Techno-economic Analysis of Solar-powered Lighting of Bali above Seawater Toll-Road - NM Karmiathi; INS Kumara; WG Ariastina; IW Gunarta (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The objective of this studywas to obtain atechnical and economic analysis of solar-powered lighting (SPL) implementation at Bali above Seawater Toll-Road. The SPL was designed to operate 12Hours/day with average illumination ≥15-lux. Those requirements can be met byan SPL unit that consists of 2-pieces 87-W LED lights mounted on 10-m double arms pole with 2.37-m arm length and 15º tilt angle. Each LED light was powered by a 260-Wp solar panel, 24V-180AH battery and 10-A solar charge controller. Every SPL unit should be installed on the toll-road median with 22.5-m pole-spacing and required 361-units to illuminate throughout 8,122.5-m toll-road length. Benefits of SPL implementation wereelectricity saving 256.15MWh/yr and carbon emission reduction 217.98TonesCO2/yr. However, the SPL electrical-based costwas 3.9 times more expensive than conventionalstreet lighting. And based onthe investment feasibility analysis using NPI and PI techniques showed that the SPL implementation was not feasible.